Factors associated with adherence to pharmacological treatment by hypertensive patients (Research, Society and Development, 2021)
Today, arterial hypertension represents one of the most prevalent diseases in Brazil and in the world, being considered as one of the most important public health problems. It is a chronic-degenerative disease, responsible for causing morbidity in the population in developed and underdeveloped countries. The treatment adopted for the control of SAH is based on non-pharmacological and pharmacological measures. Among the non-pharmacological treatments is the adoption of physical exercise practices. Pharmacological treatment consists of taking available antihypertensive drugs. Objective: to evaluate the factors associated with adherence to pharmacological treatment by hypertensive patients in the city of Montes Claros - MG. Materials and Methods: the present work is a descriptive study, with quantitative field analyzes with cross section. The population of this research was composed of 200 hypertensive patients from the Basic Health Units of the city of both genders, selected at random by lot. Results: the prevalence of adherence to pharmacological treatment was 70% in its entirety and of these 73% are able to farm through SUS. Conclusion: Public health directly influences patients' adherence to pharmaceuticals.